2016
DOI: 10.3329/sja.v14i1.29574
|View full text |Cite
|
Sign up to set email alerts
|

Performance study of some T. aman varieties under normal transplanting and double transplanting system

Abstract: The experiment was conducted to study the performance of three T. Aman varieties (BR22, BRRI dhan46 and BRRI dhan49) under normal transplanting with 30, 45 and 60 days old seedlings and double transplanting ( 30 days + 30 days) system at Plant Physiology Division of Bangladesh Rice Research Institute, Joydebpur, Gazipur during T. Aman season, 2013. Interaction effect was significant only for days to maximum flowering and sterility percentage. BR22 required longer duration to complete flowering when transplante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 2 publications
1
4
0
Order By: Relevance
“…The pattern of yield response in BRRI dhan49 to seedling age was similar to that reported by Hasanuzzaman et al (2014) for the same variety who found decreased yield with increased seedling age of 25 day-old onward. On the contrary, no significant yield variation for seedling age in the range of 30 to 60 days was found for BRRI dhan49 (Yasmeen et al, 2016). A lower yield was achieved in both the varieties when the seedling density was used over 3 per hill; which corroborates with the var.…”
Section: Discussionsupporting
confidence: 75%
“…The pattern of yield response in BRRI dhan49 to seedling age was similar to that reported by Hasanuzzaman et al (2014) for the same variety who found decreased yield with increased seedling age of 25 day-old onward. On the contrary, no significant yield variation for seedling age in the range of 30 to 60 days was found for BRRI dhan49 (Yasmeen et al, 2016). A lower yield was achieved in both the varieties when the seedling density was used over 3 per hill; which corroborates with the var.…”
Section: Discussionsupporting
confidence: 75%
“…It has been reported that seedlings of one decimal primary nursery area can cover three decimals of area in secondary nursery and these seedlings are enough for occupying 24 decimals area in main field [33]. Yasmeen et al [21] did not find significant variations in leaf area index, dry matter accumulation at later stages of crop growth and speculated similar photosynthetic rate under various transplanting methods as the reason behind it. However, they observed higher yield attributes and yield under DT method as compared to single transplanting of similar aged seedlings (Table 7).…”
Section: Role Of Double Transplanting As a Contingency Approachmentioning
confidence: 96%
“…• Sometimes, tiller mortality (later formed tillers) is observed specifically after transplanting from secondary nursery to main field, making low growth of crop under DT system. Yasmeen et al [21] noticed lowest number of tillers at post flowering stage due to mortality of later formed tillers.…”
Section: Limitations Of Double Transplantingmentioning
confidence: 98%
See 2 more Smart Citations